PERAN MOTIVASI DAN KINERJA PENYULUH PERTANIAN DALAM MENGUBAH PERILAKU PETANI JAGUNG - Mohamad Ikbalbahua (Hasanuddin University, 2018)
The purpose of this study are: (1) identify the influence of competence that can improve the performance of agricultural extension in the development of maize farming, (2) examine the influence of competence and performance of agricultural extension on the behavior of corn farmers, and (3) analysis the impact of extension performance agriculture corn farmers on changing behaviors. Research conducted in Gorontalo Province in Maret until Juni 2018. The study was